Prenatal exposure to criteria air pollution and traffic-related air toxics and risk of autism spectrum disorder: A population-based cohort study of California births (1990–2018) - Karl O’Sharkey; Sanjali Mitra; Ting Chow; Seung-a Paik; Laura Thompson; Jason Su; Myles Cockburn; Beate Ritz (Environment International)
Background: Autism spectrum disorder (ASD) prevalence has risen steadily in California (CA) over several decades, with environmental factors like air pollution (AP) increasingly implicated. This study investigates associations between prenatal exposure to both criteria AP and traffic-related air toxics and ASD risk for 1990–2018 births. Methods: Utilizing CA Department of Public Health birth registry data from 1990 to 2018, linked with ASD diagnoses from the CA Department of Developmental Services (n = 13,591,003 children; ASD cases = 138,460, identified from birth year through 2022, allowing for a follow-up ranging from a minimum of 4 to a maximum of 32 years) we assessed prenatal exposure to PM2.5, NO2, O3, and six traffic-related air toxics (benzene, 1,3-butadiene, chromium, lead, nickel, zinc) using machine learning-enhanced land-use regression models. Logistic regression estimated odds ratios (OR) for ASD per interquartile range increase in pollutant levels across four periods (1990–1997, 1998–2004, 2005–2011, 2012–2018). Additionally, analyses were stratified by race/ethnicity, area-level socioeconomic status (SES), and region. Results: Prenatal exposure to PM2.5 (OR:1.10; 95% CI: 1.04, 1.17) and NO2 (OR:1.25; 95% CI:1.16, 1.35) were associated with increased ASD risk, with effect sizes declining over time. When mutually adjusting for NO2, the association between PM2.5 exposure and ASD risk was attenuated, whereas the association with NO2 exposure remained largely unchanged. Among air toxics, benzene (OR:1.55; 95% CI:1.51, 1.59) and nickel (OR:1.32; 95% CI:1.21, 1.45) were strongly associated with ASD, associations persisting across time. Stratified analyses revealed that associations differed by race/ethnicity, SES, and region. Air toxics consistently exhibited elevated ASD risks, highlighting persistent vulnerabilities despite reductions in criteria pollutants. Conclusions: Prenatal/early-life exposure to AP, especially traffic-related toxics, is linked to increased ASD risk with temporal and spatial variability. While reductions in NO2 and PM2.5 lessen ASD risk, persistent associations with traffic-related pollutants like benzene and nickel highlight the need for targeted interventions.